Clinical, Laboratorial and Image Aspects of a Perforated Pyloric Ulcer Secondary to Nonsteroidal Anti-Inflammatory Use in a Cat - Basualdo Junior, Tadeu; Cedron Benetti, Ester Mercado; Lanfredi Tonin, Julia; Figueiredo da Silva, Márcio Virgílio; de Araújo, Joyce Maira; Eguchi, Gabriel Utida (Acta Scientiae Veterinariae, 2020)
Background: Inappropriate use of drugs for veterinary patients represents a common problem at clinical practice. Nonsteroidal anti-inflammatories are one of these misused drugs and may lead to clinical status of challenging diagnosis. Adverse effects for patients submitted to its incorrect use may include simple cases such as pharmacological gastroenteritis to severe acute renal failure or perforated gastroenteric ulcers with no pathognomonic clinical signs. The objective of this report was to describe a case of a perforated pyloric ulcer secondary to prolonged use of meloxicam in a cat with its clinical, laboratorial and image aspects from the moment of suspicion until the diagnosis. Case: An 8-year-old female feline was attended at the Veterinary Hospital of the Dom Bosco Catholic University, with main complaint being a mammary nodule with recent ulceration. Tumor staging and pre-surgical blood analysis were performed previous to total unilateral mastectomy. Eleven days post-surgery the patient was brought for suture removal, but it was observed stupor, moderate dehydration (estimated 10%), 36.7ºC rectal temperature, heart rate at 100 beats/min, respiratory rate at 60 breaths/min, 40 mg/dL blood glucose, icterus and abdominal distension with tympany at percussion (fluid wave test was negative). Anamnesis revealed the possible use of meloxicam for 10 days. The first suspicion was sepsis, with enteric gas secondary to infection. Due to no classical signs of peritoneum effusion and possible severe enteric distension, abdominocentesis was not immediate performed. Complete blood count and serum biochemistry revealed a marked band leukocytosis associated with renal injury, supporting the first sepsis suspicion. Abdominal radiography revealed radiodensity of diffuse aspect at ventral topography but no evidence of marked enteric distension that would justify tympany. Abdominal ultrasound identified effusion predominantly hyperechogenic with hyperechogenic mesentery, indicative of peritonitis. A diagnostic abdominocentesis was performed revealing a dense yellow-green effusion with high suspicion of being gastroenteric liquid. Exploratory laparotomy was not authorized by the owner and the patient was submitted to euthanasia due to the bad prognosis. Macroscopic necropsy was performed and a perforated pyloric ulcer was identified along with an impregnated mesentery with a green-brown color (peritonitis), closing the diagnosis. Discussion: The importance of reiteration regarding veterinary prescription orientation, especially for feline patients, is evidenced. Along the indiscriminate over-the-counter sale of veterinary drugs, self-medication prior to veterinary consultation is usual even for ongoing assisted patients. Considering the unspecific clinical signs that patients with perforated gastroenteric ulcers may present, the diagnosis may be challenging when no complementary image exams are immediate available. The stuporous mental state inhibiting possible manifestation of abdominal discomfort, absence of positive fluid wave test and tympany at percussion which prohibited a secure abdominocentesis could have led to a delay in diagnosis, if not for image support. Considering the emergency status of these patients, early diagnosis is crucial, therefore clinicians should have precaution when approaching patients with possible perforated gastroenteric ulcers and trust clinical history, even when classical signs of abdominal effusion are not present.